2020
DOI: 10.1002/aenm.202002521
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Doping of P3HT with Largely Soluble Tris(pentafluorophenyl)borane for Highly Conductive and Stable Organic Thermoelectrics Via One‐Step Solution Mixing

Abstract: Molecular doping is essential for improving the thermoelectric properties of conjugated polymers, but dopants of low solubility either restrict the formation of high quality films or complicate fabrication steps. Although a highly soluble molecular dopant, tris(pentafluorophenyl)borane (BCF), has been sporadically studied, its potential has not yet been fully explored. Herein, particularly intriguing effects of Brønsted acid doping with BCF‐water complexes for poly(3‐hexylthiophene) (P3HT) are reported, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 65 publications
(142 reference statements)
1
68
0
Order By: Relevance
“…Meanwhile, the strong electron-withdrawing capability of A moiety could strengthen the energetic disorder along the polymer chains and tuning the shape of density-ofstates (DOS), thus enlarging the value of E F − E T , which is proportional to S. [27] Accordingly, the peak room-temperature PFs of PBDP-T, PTB7-Th, and PBDB-T are acquired to be as high as 20.1, 46.0, and 105.5 μW m −1 K −2 at [FeCl 3 ] = 10, 5, and 10 mM, respectively, as shown in Figure 4c. When comparing with the literature results of D-𝜋, [14][15][16][17][18][19][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] A-𝜋, [20,[49][50][51] and D-A [23][24][25][26][27][52][53][54] type copolymers as summarized in Figure 4d, it has been rarely reported with S values over 100 μV K −1 , most of which were obtained by those D-A copolymers. This work achieves an impressively high PF over 100 μW m −1 K −2 while preserving a superior S beyond 200 μV K −1 as shown in Table S6, Supporting Information, holding great promise in wearable skin electronics, taken as one example.…”
Section: Resultsmentioning
confidence: 89%
“…Meanwhile, the strong electron-withdrawing capability of A moiety could strengthen the energetic disorder along the polymer chains and tuning the shape of density-ofstates (DOS), thus enlarging the value of E F − E T , which is proportional to S. [27] Accordingly, the peak room-temperature PFs of PBDP-T, PTB7-Th, and PBDB-T are acquired to be as high as 20.1, 46.0, and 105.5 μW m −1 K −2 at [FeCl 3 ] = 10, 5, and 10 mM, respectively, as shown in Figure 4c. When comparing with the literature results of D-𝜋, [14][15][16][17][18][19][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] A-𝜋, [20,[49][50][51] and D-A [23][24][25][26][27][52][53][54] type copolymers as summarized in Figure 4d, it has been rarely reported with S values over 100 μV K −1 , most of which were obtained by those D-A copolymers. This work achieves an impressively high PF over 100 μW m −1 K −2 while preserving a superior S beyond 200 μV K −1 as shown in Table S6, Supporting Information, holding great promise in wearable skin electronics, taken as one example.…”
Section: Resultsmentioning
confidence: 89%
“…Meanwhile, the CH out-of-plane bending vibration peak of thiophene in P3CT-K shifts from 820 to 816 cm −1 , which suggests the coordination interaction between the lone pair of the thiophene and the empty p-orbital of TPB, as has been reported. [23][24][25] The UV-vis absorption spectra of P3CT-K with or without TPB are shown in Figure 1b. The absorption peak of P3CT-K(TPB) displays an obvious blueshift from 546 to 517 nm comparing with that of P3CT-K after TPB addition.…”
Section: Resultsmentioning
confidence: 99%
“…However, the resultant polymer exhibits poor solubility in the solvents, thereby restricting the applicability. Following this, Bronsted acid and Lewis acid dopants comparative studies revealed that the Bronsted acid doped P3HT lead to the delocalized length increase because of enhanced crystallinity and backbone planarization contributions [156]. As an alternative approach, molecular structure and crystallinity fine-tunements of the polythiophene remains crucial in glorifying the high charge carrier mobility of the transistors.…”
Section: Polythiophene Sensorsmentioning
confidence: 99%